A Tale of Two Codes: Examining § 522(f) of the Bankruptcy Code, § 9-103 of the Uniform Commercial Code and the Proper Role of State Law in Bankruptcy - Juliet M. Moringiello (Washington University Law Quarterly, 2001)
There are several reasons why Congress should define the term “purchase-money security interest” in the Code. First, allowing judicial definitions of the term “purchase-money security interest” leads to uncertainty, which is undesirable from both a bankruptcy law and commercial law perspective. In addition, in a consumer goods transaction, purchase-money status is irrelevant outside of bankruptcy. A federal solution to the problem is appropriate and within Congress’ constitutional authority to establish “uniform Laws on the subject of Bankruptcies throughout the United States.” The Bankruptcy Code already modifies numerous property rights. In fact, § 522(f) allows a debtor to set aside a security interest that would be valid under state law. Congress has already refined § 522(f) once to eliminate a perceived ambiguity in the statute and has clarified other property rights under the Code. Finally, because of the policies underlying consumer bankruptcy law, the problem of defining purchase-money security interests is one that needs a national solution.
Keywords: Collateral security -- United States -- States; Bankruptcy exemptions; Bankruptcy law; Preemption (Legislative power); Priorities of claims and liens; Secured transactions; Bankruptcy Code of 1978; Uniform Commercial Code